Experience in Implementing Remote Laboratory Experiment Technology - Imnaishvili, Levan; Bedineishvili, Maguli; Donadze, Mikheil (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
The work concerns the implementation of remote experimentation in engineering education. For this purpose, an original technological platform for remote laboratory experiments and a teaching model are used. The technological platform involves the remote implementation of a laboratory experiment in an educational institution with appropriate equipment, while students are in an interactive computer classroom equipped for remote experimentation at another university. The work describes the architecture of the technological platform and the teaching model. The results of a student satisfaction survey are presented. Therefore, the work discusses both positive results and existing challenges.